Influence of microstructure of lactone‐based triblock copolymers on drug release behavior of their microspheres. Issue 37 (25th May 2017) - Kasyapi, Nibedita; Dinesh Kumar, K.; Bhowmick, Anil K.
ABSTRACT: The current work focuses on the influence of microstructure of different lactone‐based triblock copolymers on drug delivery, where the middle segment was δ‐valerolactone or ɛ‐caprolactone and the terminal segment wasd, l ‐lactide or cis ‐lactide. Microspheres were fabricated from the triblocks using salicylic acid as the model drug. The microsphere formation and drug release were investigated by scanning electron microscopy, ultraviolet–visible spectroscopy, X‐ray diffraction, and thermogravimetry. The size of the microspheres ranged from 2 to 20 µm in diameter. The diffusion coefficient values showed that replacement of the middle segment, δ‐valerolactone with ɛ‐caprolactone, retarded the diffusion of the drug molecules. The diffusion coefficient was lowered whend, l ‐lactide content was decreased in the triblock. Mathematical models were used to predict the drug release from the microspheres of different triblocks. The modeling study on drug release profiles revealed that the biodegradable nature of the triblock played a crucial role in determining the drug release kinetics. The diffusion and degradation reaction justified the drug release from microsphere. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45284. Abstract :